Positive electrode active material for all-solid-state lithium ion secondary battery and method for producing same
By using lithium nickel composite oxide with a specific crystal structure and coating as the positive electrode active material, the problem of reducing the charge and discharge cycle capacity of all solid lithium ion secondary batteries at high voltage is solved, and the cycle capacity maintenance rate of the battery is improved and Thermal stability and efficient manufacturing method is realized.
Patent Information
- Application Number
- CN202380042284.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-10
AI Technical Summary
In all-solid-state lithium-ion secondary batteries, after the existing positive electrode active substances are repeatedly charged and discharged at high voltage, the charge and discharge cycle capacity is significantly reduced, and there is a difference between the capacity and the initial capacity.
Li-nickel composite oxide having a specific crystal structure and a coating layer is used as the positive electrode active material, which includes lithium-nickel composite oxide particles and a coating layer. The lithium-nickel composite oxide particles have an R-3m crystal structure, including Li, Ni, Mn and other elements, and the coating layer consists of specific elements, is prepared by mixing, firing and coating process to ensure particle size distribution and uniformity of the coating layer.
The charging and discharging cycle characteristics of all solid lithium-ion secondary batteries are improved, the circulation capacity maintenance rate and thermal stability of the battery are enhanced, and a high productivity manufacturing method is realized.
Smart Images

Figure CN119301775A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material for an all-solid-state lithium-ion secondary battery and a method for producing the same. Background Art
[0002] In recent years, with the increase of environmental awareness, the transition from gasoline vehicles to hybrid vehicles and electric vehicles has been advancing, and in particular, there is a strong desire to develop small and lightweight secondary batteries with high energy, which are essential for the popularization of electric vehicles. As such secondary batteries, there is a lithium ion secondary battery.
[0003] At present, common lithium-ion secondary batteries use lithium transition metal composite oxides such as LiCoO2, LiNiO2, and LiMn2O4 as positive electrode active materials, and use lithium metal, lithium alloys, metal oxides, carbon, etc. as negative electrode active materials.
[0004] When a non-aqueous electrolyte is used as the electrolyte, for example, an electrolyte in which a Li salt such as LiClO 4 or LiPF 6 is dissolved as a supporting salt in an organic solvent such as ethylene carbonate, dimethyl carbonate, or ethyl methyl carbonate is used.
[0005] Among the components of lithium-ion secondary batteries, non-aqueous electrolytes in particular are the main reason for limiting battery performance such as high-speed charging, thermal stability, and life due to chemical properties such as heat resistance and potential window. Therefore, all-solid-state lithium-ion secondary batteries (hereinafter also referred to as "all-solid-state batteries") that improve the above-mentioned battery performance by using solid electrolytes instead of non-aqueous electrolytes as electrolytes are currently being actively researched and developed.
[0006] For example, it is described in Patent Document 1 that: Among solid electrolytes, sulfide solid electrolytes have high lithium ion conductivity during charge and discharge, and are preferably used in all-solid-state batteries. However, as disclosed in Non-Patent Document 1, when a sulfide solid electrolyte contacts a positive electrode active material as an oxide, a reaction occurs at the interface between the solid electrolyte and the positive electrode active material during charge and discharge, and a high resistance phase is generated at the interface, which hinders the operation of the all-solid-state battery. This is because, at the contact interface, the concentration of conductive ions changes due to the difference in electrochemical potential, thereby forming a space charge layer, which becomes an ion conductivity different from the main body, and the resistance becomes higher.
[0007] Therefore, for example, Patent Document 2 proposes a technique for providing a coating layer composed of LiNbO 3 on the surface of a positive electrode active material in order to prevent a solid electrolyte from contacting the positive electrode active material (oxide) and suppress the generation of a high resistance phase.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2014-056661
[0011] Patent Document 2: Japanese Patent Application Publication No. 2010-170715
[0012] Patent Document 3: Japanese Patent Application Publication No. 2011-116580
[0013] Non-patent literature
[0014] Non-patent document 1: Narumi Ohta et al., "LiNbO3-coated LiCoO2 as cathode material for all solid-state lithium secondary batteries", Electrochemistry Communications 9 (2007) 1486-1490 Summary of the invention
[0015] Problems to be solved by the invention
[0016] However, in order to realize the high energy density of lithium ion secondary batteries, it is preferred to charge and discharge the battery at a high voltage, and it is preferred to use a positive electrode active material with a high average operating voltage. Examples of such positive electrode active materials include LiNi 0.33 Co 0.33 Mn 0.33 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2 or the like is a positive electrode active material containing Mn and having a Ni ratio of 30% or more.
[0017] Therefore, the inventors have studied the possibility of application of the above-mentioned positive electrode active material in all-solid-state lithium ion secondary batteries. As a result, the inventors have found that for the above-mentioned positive electrode active material in the past, when repeatedly charging and discharging with high voltage, there is a problem that the capacity after repeated charge and discharge cycles is greatly reduced compared with the capacity (initial capacity) before repeated charge and discharge cycles.
[0018] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a positive electrode active material having improved charge-discharge cycle characteristics as a positive electrode active material for an all-solid-state battery.
[0019] Means for solving problems
[0020] In a first aspect of the present invention, a positive electrode active material for an all-solid-state lithium-ion secondary battery is provided, which has particles of a lithium nickel composite oxide and a coating layer covering the particle surface. Among them, the particles of the lithium nickel composite oxide have a crystal structure belonging to the space group R-3m, and contain at least Li, Ni, Mn, and element M. The molar ratio of each element is represented by Li:Ni:Mn:M = a:(1-x-y):x:y (0.95 ≤ a ≤ 1.10, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 < x + y ≤ 0.7, and element M is at least one selected from the group consisting of Co, Al, Zr, Si, Zn, Nb, and Ti). The Li site occupancy rate is 92% or more and 98.5% or less. In the cumulative volume distribution curve of the particle size distribution, the particle diameter (D50) corresponding to a cumulative volume ratio of 50% is 8 μm or less. The crystallite diameter calculated by the Scherrer method from the diffraction peak attributed to the (003) plane measured by XRD is 70 nm or more and 140 nm or less. The amount of eluted lithium ions determined by neutralization titration is 0.05 mass% or more and 0.50 mass% or less relative to the total amount of the particles of the lithium nickel composite oxide. The coating layer is a composite oxide containing Li and at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W).
[0021] In addition, the particles of the lithium nickel composite oxide contain secondary particles formed by aggregation of a plurality of primary particles, and have a porous structure in which there are a plurality of void portions where no primary particles exist in the secondary particles. The specific surface area measured by the nitrogen adsorption BET method is preferably 0.3 m 2 / g or more and 2.0 m 2 / g or less. In addition, the average thickness of the coating layer is preferably 1 nm or more and 15 nm or less.
[0022] In a second aspect of the present invention, a method for manufacturing the above-mentioned positive electrode active material for an all-solid-state lithium-ion secondary battery is provided, which includes: a mixing step of mixing a nickel composite compound and a lithium compound to obtain a mixture; a firing step of firing the mixture to obtain particles of a lithium nickel composite oxide; and a coating step of causing a coating liquid containing at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W to adhere to the surface of the particles of the lithium nickel composite oxide to form a coating layer.
[0023] In addition, the nickel composite compound contains a nickel composite oxide, and preferably includes an oxidation roasting step of oxidizing and roasting a nickel composite hydroxide adjusted by a crystallization reaction to obtain a nickel composite oxide. In addition, a heat treatment step of heat-treating the particles of the lithium nickel composite oxide having a coating layer formed on the surface at 300 °C or higher is preferably provided after the coating step.
[0024] Advantages of the Invention
[0025] The positive electrode active material of the present invention improves the charge-discharge cycle characteristics when used as a positive electrode active material of an all-solid-state battery. In addition, the production method of the present invention can produce the positive electrode active material with high productivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram showing an example of the positive electrode active material according to the present embodiment.
[0027] Figure 2 This is a diagram showing an example of a method for producing a positive electrode active material according to this embodiment.
[0028] Figure 3 This is a diagram showing an example of a method for producing a nickel composite compound according to the present embodiment.
[0029] Figure 4 It is an explanatory diagram of the cross-sectional structure of an evaluation battery used for battery evaluation. DETAILED DESCRIPTION
[0030] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings. It should be noted that in the accompanying drawings, in order to facilitate the understanding of each structure, a part is emphasized or a part is simplified for representation, and sometimes the actual structure or shape, scale, etc. are different. In addition, the present invention is not limited to the following embodiments, and various deformations and substitutions can be made to the following embodiments without departing from the scope of the present invention.
[0031] 1. Positive electrode active material for all-solid-state lithium-ion secondary batteries
[0032] First, a configuration example of a positive electrode active material for an all-solid-state lithium ion secondary battery (hereinafter also simply referred to as “positive electrode active material”) according to the present embodiment will be described.
[0033] Figure 1 Schematically shows an example of a positive electrode active material according to this embodiment. Figure 1 As shown, the positive electrode active material 10 includes particles 1 of a lithium nickel composite oxide and a coating layer 2 that covers the surface of the particles 1. Hereinafter, each component will be described.
[0034] (1) Lithium Nickel Composite Oxide Particles
[0035] The lithium nickel composite oxide particle 1 is a composite oxide having a crystal structure belonging to the space group R-3m and containing at least lithium (Li), nickel (Ni), manganese (Mn) and the element M.
[0036] (composition)
[0037] In the case of the molar ratio of the amounts of substances of the respective elements contained in the particles 1 of the lithium nickel composite oxide represented by Li:Ni:Mn:M = a:(1 - x - y):x:y, 0.95 ≤ a ≤ 1.10, 0 < x ≤ 0.5, 0 < y ≤ 0.5, and 0 < x + y ≤ 0.7 are satisfied. Further, in the above molar ratio, it is preferable that 0.97 ≤ a ≤ 1.08, 0 < x ≤ 0.3, 0 < y ≤ 0.3, and 0 < x + y ≤ 0.5.
[0038] In the above molar ratio, a representing the content ratio of Li is 0.95 ≤ a ≤ 1.10, and it may also be 0.97 ≤ a ≤ 1.08. When a is less than 0.95, Li is lacking in the positive electrode active material, which easily leads to a decrease in the capacity as a battery material. On the other hand, when a is greater than 1.10, the crystal structure of the particles 1 of the lithium nickel composite oxide grows excessively, the primary particles become thick, and cracks in the particles 1 are likely to occur, so the durability is easily impaired. In addition, a may be 1.00 or more, or may be greater than 1.00.
[0039] In the above molar ratio, (1 - x - y) representing the content ratio of Ni is 0.3 or more and less than 1.0, preferably 0.5 or more and less than 1.0. Further, the lower limit range of the content ratio of Ni is preferably 0.6 or more, and it may also be 0.7 or more. The higher the content ratio of (1 - x - y), the lower the voltage required for charging, and as a result, the higher the battery capacity. On the other hand, from the viewpoint of appropriately performing charge and discharge at a high voltage, the upper limit of the content ratio of (1 - x - y) can be 0.9 or less, or can be 0.85 or less. When (1 - x - y) is less than 0.3, the battery capacity becomes low.
[0040] In the above molar ratio, x representing the content ratio of Mn is 0 < x ≤ 0.5, and it may be 0 < x ≤ 0.4 or less, or may be 0 < x ≤ 0.3 or less. When the content ratio of Mn is in the above range, a high battery capacity and high thermal stability can be achieved. In addition, the lower limit of x representing the content ratio of Mn can be, for example, 0.05 or more.
[0041] In the above molar ratio, the element M is preferably at least one selected from the group consisting of Co, Al, Zr, Si, Zn, Nb, and Ti. Further, the element M preferably contains at least one element selected from cobalt (Co) and aluminum (Al), may contain cobalt (Co) and aluminum (Al), and more preferably contains cobalt (Co). The element M can be appropriately selected according to the use and required performance of the secondary battery constituted by the positive electrode active material 10. It should be noted that the element M may not contain Nb.
[0042] In the above molar ratios, y representing the content ratio of element M is 0 < y ≤ 0.5, preferably 0 < y ≤ 0.3, and may also be 0 < y ≤ 0.2. For example, when element M contains Co and Co is included within the above range of y, it has a high battery capacity and more excellent cycle characteristics. In addition, when element M contains Co, the range of Co (y1) can be, for example, 0 < y1 ≤ 0.3, or may also be 0 < y1 ≤ 0.2. Further, when element M contains Al, the range of Al (y2) can be, for example, 0 < y2 ≤ 0.1, or may also be 0 < y2 ≤ 0.07.
[0043] (Crystal structure)
[0044] The particles 1 of the lithium nickel composite oxide have a crystal structure belonging to the space group R-3m. When the particles 1 of the lithium nickel composite oxide have a crystal structure belonging to the space group R-3m, in a secondary battery, an increase in internal resistance can be suppressed.
[0045] The crystal structure of the particles 1 of the lithium nickel composite oxide can be confirmed by powder X-ray diffraction (XRD) measurement. That is, preferably, from the diffraction pattern obtained in the case of performing powder X-ray diffraction (XRD) measurement on the particles 1 of the lithium nickel composite oxide, peaks attributable to the layered rock salt-type crystal structure (crystal structure belonging to the space group R-3m) of "R-3m" structure are detected. In particular, it is more preferable to detect only the peaks attributable to the layered rock salt-type crystal structure of "R-3m" structure from the above diffraction pattern.
[0046] It should be noted that the particles 1 of the lithium nickel composite oxide may be a single phase of the lithium nickel composite oxide having a crystal structure of "R-3m" structure, or may not be a single phase. When it is not a single phase but contains other compounds (such as impurities, etc.), it is preferable that the intensity of the heterogeneous peaks other than the layered rock salt-type structure of "R-3m" structure does not exceed the peak intensity of the layered rock salt-type structure belonging to "R-3m" structure.
[0047] (Li site occupancy)
[0048] The Li site occupancy of the positive electrode active material is 90% or more and 98.5% or less, and may be 90% or more and 98% or less, 92% or more and 98% or less, or 93% or more and 98% or less. The Li site occupancy represents the proportion of lithium (Li) of the lithium metal composite oxide in the lithium layer (Li site) of the layered structure. When the lithium site occupancy of the positive electrode active material is within the above range, it is believed that a cation mixing occurs in the positive electrode active material in which metals other than lithium move to the lithium ion site. When charging and discharging at a high voltage, it is believed that the positive electrode active material in which a cation mixing occurs at a specific ratio has a high charge and discharge capacity, while the expansion and contraction of the volume is suppressed, and the cycle capacity retention rate (durability) is improved.
[0049] In addition, the lower limit of the Li site occupancy can be 90% or more, 92% or more, 93% or more, or 95% or more. In addition, the upper limit of the Li site occupancy can be 98.5% or less, or 98% or less. When the Li site occupancy is, for example, 92% or more and 98.5% or less, it has a high charge and discharge capacity, and the expansion and contraction of the volume is suppressed, which can improve the cycle capacity maintenance rate (durability). The particles 1 of the lithium nickel composite oxide are set to the specific ranges described later, and the Li site occupancy is set to the above range, so that when charging and discharging at a high voltage, it is possible to take into account both the battery capacity and the charge and discharge cycle capacity maintenance rate at a high level.
[0050] It should be noted that the evaluation method of the Li site occupancy is not particularly limited, for example, it can be obtained by performing a full spectrum fitting analysis (Rietveld analysis) on the diffraction pattern obtained by using the X-ray diffraction method (XRD). As an X-ray diffraction device (XRD), for example, X'PertPRO (Spectris Co., Ltd.) can be used. In addition, for the diffraction pattern obtained by measuring the positive electrode active material, for example, in addition to the commonly widely used RIETAN-FP, analysis programs such as High_Score_Plus (Spectris Co., Ltd.) and JADE_PRO (Materials_Data Co., Ltd.) can be used for full spectrum fitting analysis to obtain the Li site occupancy.
[0051] (Crystallite diameter)
[0052] The crystallite diameter of the particle 1 of the lithium nickel composite oxide is preferably less than 140nm, more preferably more than 70nm and less than 140nm. In addition, the range including the upper limit of the crystallite diameter can be less than 130nm. It should be noted that the crystallite diameter can be calculated by the Scherrer method using the peak belonging to (003) of the above-mentioned XRD diffraction pattern. In the case where the crystallite diameter of the particle 1 of the lithium nickel composite oxide is greater than 140nm, sometimes the solid diffusion distance in the crystal becomes longer and the battery capacity is reduced. In addition, in the case where the crystallite diameter of the particle 1 of the lithium nickel composite oxide is less than 70nm, the crystal structure becomes unstable and the battery capacity is easily reduced. In addition, the lower limit of the crystallite diameter can be more than 70nm, can be more than 90nm, or can be more than 100nm. In addition, the upper limit of the crystallite diameter can be less than 140nm, can be less than 130nm, or can be less than 125nm.
[0053] (Amount of dissolved lithium ions)
[0054] Regarding the particles 1 of the lithium nickel composite oxide, the amount of eluted lithium ions obtained by neutralization titration is 0.05 mass % or more and 0.50 mass % or less, preferably 0.05 mass % or more and 0.40 mass % or less, relative to the total amount of the particles 1. It should be noted that the amount of eluted lithium ions can be obtained by neutralization titration using hydrochloric acid when the particles 1 of the lithium nickel composite oxide are dispersed in water. As the neutralization titration method, the Warder method and the Winkler method can be used.
[0055] In addition, in the positive electrode active material involved in the present embodiment, the amount of dissolved lithium ions may be less than 0.30% by mass, or less than 0.25% by mass. In addition, the amount of dissolved lithium ions may be greater than 0.10% by mass. When the amount of dissolved lithium ions is within the above range, sufficient battery capacity can be achieved. When the amount of dissolved lithium ions in the particles 1 of the lithium nickel composite oxide is less than 0.05% by mass, the battery capacity is sometimes reduced. The details of the reason are not yet clear, but it is believed that one of the reasons is that, for example, by including a specific amount of dissolved lithium ions on the surface of the particles 1 of the lithium nickel composite oxide, the direct contact between the particles 1 of the lithium nickel composite oxide and the solid electrolyte is suppressed in the all-solid-state battery, thereby suppressing the generation of a high-resistance phase.
[0056] (Particle structure)
[0057] The lithium nickel composite oxide particle 1 includes secondary particles formed by agglomeration of a plurality of primary particles. The lithium nickel composite oxide particle 1 may include primary particles alone or may be a mixture of primary particles alone and secondary particles.
[0058] When observed by scanning electron microscope (SEM), transmission electron microscope (TEM), etc., the average particle size of the secondary particles is preferably less than 8.0 μm, preferably more than 3.0 μm and less than 8.0 μm. In addition, the secondary particles are preferably formed by a large amount of agglomeration of primary particles having a particle size of more than 0.1 μm and less than 2.0 μm. In addition, in the case of containing a single primary particle, the primary particle preferably has a particle size of more than 1.0 μm and less than 8.0 μm. It should be noted that the average particle size of each particle can be obtained, for example, by calculating the average of the area equivalent circle diameters of more than 20 particles.
[0059] (Average particle size D50)
[0060] The particle size (D50, hereinafter also referred to as "average particle size D50") of the lithium nickel composite oxide particles 1 in the cumulative volume distribution curve of the particle size distribution is preferably 8 μm or less, more preferably 2 μm or more and 8 μm or less, more preferably 2 μm or more and 7 μm or less, and further preferably 3 μm or more and 7 μm or less. It should be noted that the average particle size (D50) refers to the particle size (D50) in the cumulative volume distribution curve of the particle size distribution measured by a laser diffraction scattering particle size analyzer when the cumulative volume rate is 50%.
[0061] When the average particle size D50 of the lithium nickel composite oxide particles 1 is within the above range, the secondary battery using the positive electrode active material 10 for the positive electrode can improve the capacity retention rate after the cycle measurement at high voltage, and can obtain excellent battery characteristics such as thermal stability and high output power. It should be noted that when the average particle size D50 is less than 2 μm, it is easy to aggregate when the coating layer 2 is applied.
[0062] (Span of particle size distribution)
[0063] The index [(d90-d10) / volume average particle size Mv] representing the span of the particle size distribution of the lithium nickel composite oxide particle 1 is not particularly limited, and from the viewpoint of making the particle size uniform, it can be less than 0.7, less than 0.6, or less than 0.55. When the particle size is relatively uniform, it is easy to uniformly coat the coating layer 2 on the surface of the lithium nickel composite oxide particle 1, and good output characteristics can be obtained in the secondary battery. It should be noted that the lower limit of [(d90-d10) / volume average particle size Mv] is not particularly limited, for example, it is greater than 0.3. In addition, from the viewpoint of filling property, [(d90-d10) / volume average particle size Mv] can be greater than 0.7, and by using the method for manufacturing the positive electrode active material described later, the coating layer 2 can be relatively uniformly coated.
[0064] It should be noted that d10 refers to the particle size when the number of particles of each particle size is accumulated from the side with a smaller particle size, and its cumulative volume becomes 10% of the total volume of all particles, and d90 also refers to the particle size when the cumulative number of particles is accumulated, and its cumulative volume becomes 90% of the total volume of all particles. In addition, d10, d90 and volume average particle size Mv can be obtained by the volume cumulative value obtained by measuring using a laser diffraction scattering particle size analyzer in the same way as the average particle size D50.
[0065] (Specific surface area)
[0066] The specific surface area of the lithium nickel composite oxide particles 1 is not particularly limited, and may be, for example, 0.3 m 2 / g or more and 2.0m 2 / g or less, and can also be 0.3m 2 / g or more and 1.0m 2 / g or less. When the specific surface area is within the above range, the output characteristics are good. It should be noted that the specific surface area can be measured by the nitrogen adsorption BET method. In addition, the lower limit of the specific surface area can be 0.35m 2 / g or more, and can also be 0.40m 2 / g or above.
[0067] (2) Coating layer
[0068] The positive electrode active material 10 includes a coating layer 2 on the surface of a lithium nickel composite oxide particle 1. The coating layer 2 on the surface of the particle 1 can suppress the mutual reaction between the positive electrode active material 10 and the solid electrolyte in a secondary battery including a positive electrode including the positive electrode active material 10.
[0069] The coating layer 2 is a composite oxide containing lithium (Li) and one or more elements selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta and W. It should be noted that the constituent elements of the coating layer 2 other than lithium (Li) and oxygen (O) may be one or more. The coating layer 2 may be, for example, a composite oxide consisting of Li and Ti, or a composite oxide consisting of Li and Nb.
[0070] (Contents of the elements in the coating layer)
[0071] The coating amount of the coating layer 2 is not particularly limited and can be determined based on the specific surface area (m 2 / g) to adjust the coating amount. For example, per 1m 2The coating layer 2 contains the constituent elements of the coating layer 2 (excluding Li and O) in a ratio of preferably 30 μmol to 600 μmol, more preferably 50 μmol to 400 μmol, based on the surface area.
[0072] In the case of lithium nickel composite oxide particles 1m 2 When the content of the constituent elements (excluding Li and O) of the coating layer 2 per surface area is 30 μmol or more, the coating layer 2 can be uniformly arranged on the entire surface of the lithium nickel composite oxide particle 1 .
[0073] In addition, the coating layer can suppress the reaction between the lithium nickel composite oxide particles 1 and the solid electrolyte, but at the same time, the internal resistance of the secondary battery may increase. 2 When the content of the constituent elements (excluding Li and O) of the coating layer 2 per surface area is 600 μmol or less, the coating layer 2 can be prevented from becoming an obstacle to lithium insertion / extraction reaction in the lithium nickel composite oxide particles 1, thereby reducing the internal resistance.
[0074] In the coating layer 2, the method for evaluating and calculating the content of the constituent elements (excluding Li and O) of the coating layer 2 is not particularly limited, and can be determined, for example, as follows.
[0075] First, the content of the constituent elements (excluding Li and O) of the coating layer 2 in 1 g of the positive electrode active material is measured by chemical analysis or the like. As a method of chemical analysis, measurement is performed by ICP (Inductively Coupled Plasma) emission spectroscopy or the like.
[0076] On the other hand, the specific surface area of the lithium nickel composite oxide particle 1 before being coated with the coating layer 2 is measured by the nitrogen adsorption BET method or the like.
[0077] Next, the content of the constituent elements (excluding Li and O) of the coating layer 2 in 1 g of the positive electrode active material is divided by the specific surface area (m 2 / g), the mass per 1m2 of the lithium nickel composite oxide particle 1 can be calculated. 2 Content of constituent elements (excluding Li and O) of the coating layer 2 per surface area.
[0078] It should be noted that, when the particles 1 of the lithium nickel composite oxide contain the constituent elements of the coating layer 2 (excluding Li and O), the difference in the content of the constituent elements (excluding Li and O) of the coating layer 2 before and after coating can be used as the content of the constituent elements (excluding Li and O) of the coating layer 2 used for coating.
[0079] (Average thickness of coating layer)
[0080] The average thickness of the coating layer is, for example, preferably from 2 nm to 20 nm, more preferably from 2 nm to 15 nm, and even more preferably from 5 nm to 15 nm.
[0081] It should be noted that the average thickness of the coating layer 2 can be calculated as follows: by observing with a scanning electron microscope (SEM), a transmission electron microscope (TEM), etc., or analyzing with a spectrometer such as an energy dispersive X-ray spectrometer (EDS) or an electron energy loss spectroscopy (EELS) attached thereto, the layer uniformly formed on the surface of the particles 1 of the lithium nickel composite oxide is measured and calculated. It should be noted that, in the case where the thickness of the coating layer 2 varies depending on the measurement site, the thickness of the coating layer 2 refers to the average value when measuring multiple sites. In addition, the average thickness of the coating layer can also be greater than 1 nm and less than 15 nm.
[0082] (Configuration of coating layer)
[0083] In addition, the coating layer 2 is preferably present adjacent to the surface of the lithium nickel composite oxide particle 1. Whether the coating layer 2 is present adjacent to the surface of the particle 1 can be determined by whether the compound containing the constituent elements of the coating layer 2 is free from the surface of the lithium nickel composite oxide particle 1. When the coating layer 2 is free from the surface of the lithium nickel composite oxide particle 1, it does not contribute to the battery capacity electrochemically, and thus becomes a major factor in reducing the battery capacity per unit weight.
[0084] It should be noted that the coating layer 2 and the surface of the lithium nickel composite oxide particle 1 may not have a clear boundary line. For example, when the lithium nickel composite oxide particle 1 before coating does not contain the constituent elements of the coating layer 2 (excluding Li and O), the coating layer 2 refers to the region where the constituent elements of the coating layer 2 (excluding Li and O) are detected, and may also include the region where both the constituent elements of the coating layer 2 (excluding Li and O) and the elements constituting the lithium nickel composite oxide particle 1 are detected. In addition, when the lithium nickel composite oxide particle 1 before coating contains the constituent elements of the coating layer 2 (excluding Li and O), it refers to the region on the surface side of the particle constituting the positive electrode active material 10, and the concentration of the constituent elements of the coating layer 2 (excluding Li and O) is higher than the central part of the lithium nickel composite oxide particle 1.
[0085] In addition, the constituent elements of the coating layer 2 (excluding Li and O) may also be partially dissolved from the surface of the lithium nickel composite oxide particles into the interior. For example, a heat treatment step (S40) is performed after the coating step (S30), and depending on the conditions at this time, the constituent elements of the coating layer can be diffused into the lithium nickel composite oxide.
[0086] For example, when Ti and / or Nb are contained in the coating layer 2, Ti and / or Nb are dissolved from the surface of the lithium nickel composite oxide particle 1 to the inside, so that the coating layer 2 not only prevents the solid electrolyte from directly contacting the lithium nickel composite oxide particle 1 to reduce the chance of reaction, but also produces an effect of reducing the reactivity between the surface layer of the lithium nickel composite oxide particle 1 and the solid electrolyte. It should be noted that in the positive electrode active material 10, in order to fully exert the effect of improving the cycle characteristics, it is preferable to adjust the degree of solid solution.
[0087] 2. Method for producing positive electrode active material for all-solid-state lithium-ion secondary battery
[0088] Next, a method for producing a positive electrode active material for an all-solid-state lithium ion secondary battery (hereinafter also referred to as "positive electrode active material") according to this embodiment is described. By using the production method of this embodiment, the positive electrode active material 10 described above can be produced with high productivity.
[0089] Figure 2 , Figure 3 1 is a diagram showing an example of a method for producing a positive electrode active material according to this embodiment. Figure 2 As shown, the manufacturing method of the positive electrode active material of this embodiment comprises: a mixing step (S10) of mixing a nickel composite compound and a lithium compound to obtain a mixture; a calcining step (S20) of calcining the mixture to obtain particles of lithium nickel composite oxide; and a coating step (S30) of allowing a coating liquid to adhere to the surface of the particles of the lithium nickel composite oxide to form a coating layer. Furthermore, after the coating step (S30), a heat treatment step (S40) of heat-treating the particles of the lithium nickel composite oxide with the coating layer formed on the surface at 300°C or above may be provided.
[0090] In addition, the nickel composite compound may be a nickel composite oxide obtained by oxidatively calcining a nickel composite hydroxide adjusted by a crystallization reaction. Figure 3 As shown, the nickel composite compound can be produced by a method including a crystallization step (S1) and an oxidation roasting step (S2). Each step is described in detail below. It should be noted that the following description is an example of the production method and does not limit the production method.
[0091] (Crystallization step: S1)
[0092] In the crystallization step (S1), a nickel composite hydroxide serving as a precursor of a lithium nickel composite oxide is prepared by a crystallization reaction.
[0093] For example, a raw aqueous solution is prepared using water-soluble compounds (metal compounds) of various elements so that the mass ratio of each element is equal to the mass ratio of each element contained in the target lithium nickel composite oxide particles. The prepared raw aqueous solution is supplied to a reaction tank together with an alkali metal aqueous solution and an ammonium ion donor to carry out a neutralization crystallization reaction to obtain a nickel composite hydroxide.
[0094] The raw materials of each element can be dissolved in water at the same time to make a mixed aqueous solution, so as to manufacture a raw material aqueous solution. In addition, the raw materials of each element can also be adjusted to separate aqueous solutions, so as to make separate raw material aqueous solutions. It should be noted that when there is an undesirable situation when the raw material aqueous solution is made into a mixed aqueous solution, it is preferably adjusted to separate raw material aqueous solutions for each raw material. For example, when the liquid property of the aqueous solution of each raw material is divided into acidic and alkaline, it is preferably adjusted to separate raw material aqueous solutions for each raw material.
[0095] As the raw material of each element, the metal compound used can be water-soluble, and sulfate, chloride, nitrate, etc. can be used. From the viewpoint of cost, preferably cheap sulfate. It should be noted that, when no water-soluble suitable metal compound is found in element M, etc., it is not necessary to add to the mixed aqueous solution of the raw material but to add in the oxidation roasting step (S2) and the mixing step (S10) described later.
[0096] The alkali metal aqueous solution is not particularly limited, and one or more selected from the group consisting of sodium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium hydroxide, and potassium carbonate can be preferably used.
[0097] The ammonium ion donor is not particularly limited, and one or more selected from aqueous ammonia, aqueous ammonium carbonate solution, aqueous ammonium chloride solution, and aqueous ammonium sulfate solution can be preferably used.
[0098] The shape of the reaction tank is not particularly limited, and preferably a stirrer and a temperature regulator are provided in a cylindrical container with a baffle plate inside. The stirrer preferably has a motor, a shaft, and a stirring blade. The temperature regulator is preferably in a form that heats or cools the cylindrical container by circulating a heat medium outside the cylindrical container.
[0099] In the neutralization crystallization reaction of the raw material aqueous solution, the alkali metal aqueous solution, and the ammonium ion donor in the reaction tank, it is preferred to maintain the pH and the ammonia concentration at constant values.
[0100] The pH of the aqueous solution in the reaction tank is preferably adjusted to 11.0 or more and 12.2 or less based on a liquid temperature of 25°C. For example, when preparing a nickel composite hydroxide, impurities derived from anions of the metal compounds contained in the raw aqueous solution used may sometimes be mixed into the nickel composite hydroxide. However, by making the pH value of the initial aqueous solution (in the reaction tank) be 11.0 or more, the mixing of impurities derived from anions can be suppressed. In addition, by setting the pH of the initial aqueous solution to less than 12.2, the obtained nickel composite hydroxide can be suppressed from being micronized, and a composite hydroxide with a particle size suitable for charge and discharge reactions can be obtained.
[0101] In addition, the pH of the initial aqueous solution prepared in the reaction tank may be set to 12.0 or more and 14.0 or less based on a liquid temperature of 25°C before the crystallization reaction, and after the nucleation step, the crystallization reaction (particle growth step) may be performed at a pH lower than that of the previous step. In addition, after all the raw aqueous solution is dripped, the pH of the reaction aqueous solution may be set to 12.0 or more and 14.0 or less based on a liquid temperature of 25°C, and then the crystallization reaction may be terminated.
[0102] The ammonia concentration of the aqueous solution in the reaction tank is preferably adjusted to more than 5g / L and less than 20g / L. When the ammonia concentration is set to more than 5g / L, the Ni in the raw aqueous solution (mixed aqueous solution) becomes an ammonium complex, and the speed of precipitation from the liquid phase to the solid phase as a hydroxide is reduced, so the sphericity of the particles of the nickel composite hydroxide obtained is improved. On the other hand, when the ammonia concentration is set to less than 20g / L, the solubility of the nickel forming the ammonium complex can be suppressed to rise excessively, and the amount ratio of the nickel composite hydroxide obtained can be made to be the target amount ratio more reliably. In addition, the excessive consumption of ammonia can be suppressed, and it is preferred industrially.
[0103] The atmosphere in the reaction tank is preferably a non-oxidizing atmosphere, for example, an atmosphere having an oxygen concentration of 1% by volume or less. When the atmosphere in the reaction tank is set to a non-oxidizing atmosphere, oxidation of the raw material compounds etc. can be suppressed. For example, precipitation of oxidized cobalt and manganese as microparticles can be prevented.
[0104] The temperature in the reaction tank in the crystallization step (S1) is preferably maintained at 40°C or higher and 60°C or lower, more preferably at 45°C or higher, and further preferably at 55°C or lower.
[0105] The temperature of the reaction tank rises due to the heat of reaction and the Joule heat of stirring, so by setting the temperature in the reaction tank to 40° C. or higher, no extra energy is consumed during cooling. In addition, by setting the temperature in the reaction tank to 60° C. or lower, evaporation of ammonia from the initial aqueous solution and the reaction aqueous solution can be suppressed, making it easy to maintain the target ammonia concentration.
[0106] The particles (powder) of the lithium nickel composite oxide preferably have a narrow particle size distribution and a uniform particle size. In order to prepare such particles, it is necessary to obtain particles with a uniform particle size in the nickel composite hydroxide as its precursor. As a method for obtaining such particles, patent document 3 and the like can be specifically exemplified.
[0107] (Oxidation roasting process: S2)
[0108] After the precursor crystallization step (S1), an oxidative roasting step (S2) may be performed. In the oxidative roasting step (S2), the nickel composite hydroxide obtained in the precursor crystallization step (S1) is oxidatively roasted to obtain a nickel composite oxide. In the oxidative roasting step (S2), a heat treatment is performed in an oxygen-containing atmosphere and then cooled to room temperature, thereby obtaining a nickel composite oxide.
[0109] The calcination conditions in the oxidation calcination step (S2) are not particularly limited. For example, it is preferred to calcine in an oxygen-containing atmosphere or an air atmosphere at a temperature of 500° C. or more and 700° C. or less for 1 hour or more and 12 hours or less. When the calcination temperature is set to 500° C. or more, the nickel composite hydroxide can be completely converted into a nickel composite oxide. In addition, by making the calcination temperature be below 700° C., the specific surface area of the nickel composite oxide can be suppressed from being excessively reduced, so it is preferred.
[0110] By making the roasting time be more than 1 hour, the temperature in the calcining container can be made uniform, and the reaction can be carried out uniformly, so it is preferred. In addition, even if the roasting is carried out for a long time than 12 hours, the obtained nickel composite oxide can not observe a large change, so from the viewpoint of energy efficiency, the roasting time is preferably set to below 12 hours.
[0111] The oxygen concentration in the oxygen-containing atmosphere during calcination is preferably equal to or higher than the oxygen concentration of air, that is, 20% by volume or higher. Since an oxygen atmosphere is also possible, the upper limit of the oxygen concentration of the oxygen-containing atmosphere can be 100% by volume.
[0112] It should be noted that, for example, when the compound containing element M cannot be coprecipitated in the crystallization step (S1), for example, the nickel composite hydroxide provided in the oxidation roasting step S2 can be added with the compound containing element M in a manner having the same mass ratio as the target substance and calcined. There is no particular limitation on the compound containing element M to be added, and for example, oxides, hydroxides, carbonates or mixtures thereof can be used.
[0113] In addition, after the oxidation roasting step (S2) is completed, in the case where light sintering is observed in the obtained nickel composite oxide, a crushing treatment may also be applied. It should be noted that in the oxidation roasting step (S2), at least a portion of the nickel composite hydroxide may be converted into the nickel composite oxide, and the entire nickel composite hydroxide may not be converted into the oxide.
[0114] (Mixing process: S10)
[0115] The mixing step ( S10 ) is a step of mixing a nickel composite compound and a lithium compound to obtain a lithium mixture.
[0116] The nickel composite compound is preferably at least one of a nickel composite hydroxide and a nickel composite oxide, and more preferably a nickel composite oxide. In addition, the nickel composite compound is preferably obtained by a method including the above-mentioned crystallization step (S1) and / or the oxidizing roasting step (S2).
[0117] The lithium compound is not particularly limited, and for example, lithium hydroxide, lithium nitrate, lithium carbonate, or a mixture thereof can be used. As the lithium compound, lithium hydroxide is preferably used from the viewpoint of low melting point and high reactivity.
[0118] The lithium compound may be mixed in an amount such that the lithium content is 95 atomic % to 110 atomic % or 97 atomic % to 108 atomic % based on the total of Ni, Mn and element M (Me).
[0119] (Firing process: S20)
[0120] The calcining step (S20) is a step of calcining the obtained lithium mixture to obtain particles 1 of lithium nickel composite oxide. The calcining conditions are not particularly limited, for example, it is preferably calcined at a temperature of 700°C to 1000°C in an oxygen-containing atmosphere for 1 hour to 24 hours. In addition, it is also possible to cool to room temperature after calcining to obtain particles 1 of lithium nickel composite oxide. It should be noted that the calcining conditions such as calcining temperature, calcining time, calcining atmosphere, etc. can be appropriately adjusted within the above range to obtain the desired properties (Li site occupancy, crystallite diameter, amount of dissolved lithium ions, etc.).
[0121] When the calcination temperature is set to 700° C. or higher, the crystal structure of the lithium nickel composite oxide particle 1 can be sufficiently grown. When the calcination temperature is set to 1000° C. or lower, it is possible to suppress excessive mixing of Ni atoms into the Li site in the obtained lithium nickel composite oxide particle 1. In addition, the calcination temperature may be 750° C. or higher, 800° C. or higher, or 820° C. or higher.
[0122] By making the calcination time be more than 1 hour, the temperature in the calcination container can be made uniform, and the reaction can be carried out uniformly, so it is preferred. In addition, even if the calcination is carried out for a longer time than 24 hours, no significant change is observed in the obtained lithium nickel composite oxide, so from the viewpoint of energy efficiency, the calcination time is preferably set to less than 24 hours, can be less than 12 hours, can be less than 10 hours, and can also be less than 6 hours.
[0123] In addition, as an oxygen-containing atmosphere, an atmosphere containing 80% by volume or more of oxygen is preferred. This is because by setting the oxygen concentration in the atmosphere to 80% by volume or more, the crystal structure of the lithium nickel composite oxide particle 1 can be fully grown, so it is preferred. Since it can also be set as an oxygen atmosphere, the upper limit of the oxygen concentration of the oxygen-containing atmosphere can be set to 100% by volume.
[0124] It should be noted that, after the calcining step ( S20 ), when slight sintering is observed in the obtained lithium nickel composite oxide particles 1 , a crushing treatment may be applied.
[0125] (Coating process: S30)
[0126] The coating step ( S30 ) is a step of causing a coating liquid to adhere to the surface of the obtained lithium nickel composite oxide particle 1 to form a coating layer 2 .
[0127] The coating layer 2 is formed by, for example, mixing the lithium nickel composite oxide particles 1 with a coating liquid and drying them to form the coating layer 2 on the surface of the lithium nickel composite oxide particles 1. In addition, as described later, after coating, a heat treatment step (S40) may be optionally performed in an oxygen-containing atmosphere. An example of the coating step (S30) is described below.
[0128] First, a coating liquid is prepared in a predetermined amount (coating agent preparation step). The coating agent may be selected based on the specific surface area (m2) per unit of the lithium nickel composite oxide particles 1 obtained in the calcining step (S20). 2 / g) of the coating layer 2 (excluding Li and O).
[0129] The coating liquid contains at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta and W. For example, the coating liquid can be prepared by dissolving a raw material compound containing constituent elements (excluding Li and O) of the target coating layer 2 in a solvent.
[0130] Examples of the raw material compound include one or more selected from the group consisting of alkoxides and chelates using a complex having a carbonyl group, a peroxide group, and the like.
[0131] From the perspective of uniform coating, the coating liquid only needs to be liquid when it adheres to the surface of the lithium nickel composite oxide particle 1. For example, it can be prepared by dissolving a compound containing the constituent elements of the coating layer 2 in a solvent so that it is liquid at room temperature, or it can be a low-melting-point compound containing the constituent elements of the coating layer 2, which is melted by low-temperature heat treatment.
[0132] It should be noted that the coating liquid may contain Li or may not contain Li. When the coating liquid does not contain Li, in the coating step (S30) and / or the heat treatment step (S40), the Li present in the particles 1 of the lithium nickel composite oxide reacts with the compound containing the above-mentioned constituent elements in the coating liquid to form the coating layer 2.
[0133] Next, the coating liquid is attached to the surface of the lithium nickel composite oxide particle 1. The coating liquid can be attached, for example, by mixing the lithium nickel composite oxide particle 1 with the coating liquid (mixture preparation step). A common mixer can be used for mixing. In addition, drying can be performed after mixing (drying step).
[0134] In addition, from the viewpoint of forming a more uniform coating layer 2 having a specific thickness, it is preferred to perform the mixture preparation step and the drying step in parallel, and preferably use a rolling flow coating device.
[0135] Since the coating liquid shrinks due to drying, when only one mixture preparation step and one drying step are performed, gaps may be generated in the formed coating layer 2, and the function of protecting the contact between the lithium nickel composite oxide particles 1 and the solid electrolyte cannot be fully exerted. However, when a rolling flow coating device is used, since the coating liquid is sprayed onto the lithium nickel composite oxide particles 1 flowing by the airflow heated in the device, the mixture preparation step and the drying step are repeated in parallel, and a uniform coating layer without gaps can be obtained, which is preferred.
[0136] In the drying step, it is preferred to dry at a temperature that allows the solvent of the coating agent to be sufficiently removed. For example, when a rolling flow coating device is used, the air supply temperature may be set to 80° C. or higher and lower than 300° C. In addition, after the coating treatment, additional drying may be performed using a fixed type dryer.
[0137] The atmosphere in the drying step is not particularly limited, but is preferably an inert atmosphere such as air, nitrogen, or argon supplied from a compressor equipped with a dryer in order to prevent the lithium nickel composite oxide particles 1 from reacting with moisture in the atmosphere.
[0138] (Heat treatment process: S40)
[0139] Furthermore, if necessary, after the coating step (S30), a heat treatment step (S40) may be provided for heat-treating the lithium nickel composite oxide particles 1 having the coating layer 2 formed on the surface at 300° C. or higher. The heat treatment step (S40) can make the coating layer 2 and the lithium nickel composite oxide particles 1 more firmly bonded.
[0140] The heat treatment conditions in the heat treatment step ( S40 ) are not particularly limited, but heat treatment is preferably performed in an oxygen-containing atmosphere at a temperature of 300° C. to 600° C. for 1 hour to 5 hours. The oxygen-containing atmosphere may be, for example, an air atmosphere.
[0141] The oxygen concentration in the oxygen-containing atmosphere of the heat treatment step (S40) is preferably greater than the oxygen concentration of the air atmosphere, that is, the oxygen concentration is greater than 20% by volume. By making the oxygen-containing atmosphere during the heat treatment greater than the oxygen concentration of the air atmosphere, the generation of oxygen defects inside the obtained positive electrode active material 10 can be further suppressed. The oxygen-containing atmosphere may also be an oxygen atmosphere, and the upper limit of the oxygen concentration of the oxygen-containing atmosphere is 100% by volume.
[0142] When the heat treatment temperature is 300°C or higher, impurities contained in the coating solution can be further suppressed from remaining inside the positive electrode active material 10. When the heat treatment temperature is 600°C or lower, excessive diffusion of components of the coating layer 2 can be suppressed, and the morphology of the coating layer 2 can be maintained.
[0143] When the heat treatment time is 1 hour or longer, it is possible to further suppress the impurities contained in the coating solution from remaining inside the positive electrode active material 10. In addition, even when the heat treatment time is longer than 5 hours, no significant changes are observed in the obtained positive electrode active material 10. Therefore, from the viewpoint of energy efficiency, the heat treatment time is preferably 5 hours or less.
[0144] After the heat treatment step ( S40 ), the mixture is cooled to room temperature, and a positive electrode active material having lithium nickel composite oxide particles 1 and a coating layer 2 on the surface thereof can be obtained as a final product.
[0145] It should be noted that the heat treatment step (S40) may not be performed. That is, the coating step (S30) may be performed to manufacture the positive electrode active material 10. This is because, even without the heat treatment step (S40), a coating layer can be uniformly and firmly formed on the surface of the particles of the lithium nickel composite oxide. Even without the heat treatment step, it is preferred to dry as needed to reduce and remove the solvent, water, etc. of the coating agent.
[0146] When slight sintering is observed in the positive electrode active material 10 obtained after the coating step ( S30 ) and / or the heat treatment step ( S40 ), a crushing treatment may be further performed.
[0147] 3. All-solid-state lithium-ion secondary battery
[0148] The all-solid-state lithium-ion secondary battery (hereinafter also referred to as "all-solid-state battery") of this embodiment comprises a positive electrode, a negative electrode and a solid electrolyte, and the positive electrode contains the above-mentioned positive electrode active material. Hereinafter, the all-solid-state battery of this embodiment will be described separately for each component.
[0149] It should be noted that the embodiments described below are merely illustrative, and the all-solid-state battery can be implemented in various ways after various changes and improvements based on the knowledge of those skilled in the art are implemented using the following embodiments as representatives. In addition, the use of the all-solid-state battery is not particularly limited.
[0150] (positive electrode)
[0151] The positive electrode can be formed by molding the positive electrode mixture. It should be noted that the positive electrode can be appropriately processed according to the battery used. For example, in order to increase the electrode density, a press machine or the like can also be used for pressurization and compression processing.
[0152] The positive electrode mixture may be formed by mixing the powdered positive electrode active material and a solid electrolyte.
[0153] The solid electrolyte is added to impart appropriate ion conductivity to the electrode.
[0154] The material of the solid electrolyte is not particularly limited, for example, Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 Sulfide solid electrolytes, Li7La3Zr2O 12 , Li 0.34 La 0.51 TiO 2.94 Oxide-based solid electrolytes such as Oxide, polymer-based electrolytes such as PEO.
[0155] It should be noted that a binder or a conductive additive may be added to the positive electrode mixture.
[0156] The binder plays a role in connecting and fixing the positive electrode active material. The binder used in the positive electrode mixture is not particularly limited, and for example, one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin, polyacrylic acid, etc. can be used.
[0157] The conductive material is added to impart appropriate conductivity to the electrode. The material of the conductive material is not particularly limited, and for example, graphite such as natural graphite, artificial graphite, and expanded graphite, and carbon black materials such as acetylene black and Ketjen Black (registered trademark) can be used.
[0158] In addition, the mixing ratio of each substance in the positive electrode mixture is not particularly limited. For example, the content of the positive electrode active material in the positive electrode mixture can be set to 50 parts by mass or more and 90 parts by mass or less, and the content of the solid electrolyte can be set to 10 parts by mass or more and 50 parts by mass or less.
[0159] However, the method for producing the positive electrode is not limited to the above-exemplified method, and other methods may be used.
[0160] (negative electrode)
[0161] The negative electrode can be formed by molding the negative electrode mixture.
[0162] The negative electrode is formed by substantially the same method as the above-mentioned positive electrode, although the components constituting the negative electrode mixture and the blending thereof are different, and can be subjected to various treatments as necessary, similarly to the positive electrode.
[0163] The negative electrode mixture can be prepared by mixing a negative electrode active material and a solid electrolyte. As the negative electrode active material, for example, an occlusion material capable of occluding and releasing lithium ions can be used.
[0164] The storage material is not particularly limited, for example, one or more selected from natural graphite, artificial graphite, phenolic resin and other organic compound sintered bodies, and powdered bodies of carbon materials such as coke, etc. can be used. When such a storage material is used as the negative electrode active material, as with the positive electrode, a sulfide electrolyte such as Li3PS4 can be used as a solid electrolyte.
[0165] Alternatively, the negative electrode may be a sheet-like member made of a material containing a metal that alloys with lithium, such as metallic lithium or indium.
[0166] (Solid electrolyte)
[0167] Solid electrolytes are Li + Ion-conductive solids. As the solid electrolyte, one selected from sulfides, oxides, polymers, etc. may be used alone, or two or more selected from the group consisting of sulfides, oxides, polymers, etc. may be used in combination.
[0168] As sulfide-based solid electrolytes, there are no particular limitations, and any solid electrolyte containing sulfur (S) and having lithium ion conductivity and electronic insulation can be used. Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and the like.
[0169] The oxide-based solid electrolyte is not particularly limited, and any oxide-based solid electrolyte may be used as long as it contains oxygen (O) and has lithium ion conductivity and electron insulation.
[0170] As oxide-based solid electrolytes, for example, lithium phosphate (Li3PO4), Li3PO4NX, LiBO2NX, LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≤X≤1), Li 1+X Al X Ge 2-X (PO4)3(0≤X≤1), LiTi2(PO4)3, Li3XLa 2 / 3-X TiO3(0≤X≤2 / 3), Li5La3Ta2O 12 、Li7La3Zr2O 12 、Li6BaLa2Ta2O 12 , Li 3.6 Si 0.6 P 0.4 O4, etc.
[0171] It should be noted that as the inorganic solid electrolyte, substances other than those mentioned above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.
[0172] As a polymer-based solid electrolyte, as long as it is a high molecular compound showing ion conductivity, it is not particularly limited, for example, polyethylene oxide, polypropylene oxide, their copolymers, etc. can be used. In addition, the organic solid electrolyte can include a supporting salt (lithium salt). It should be noted that, when using a solid electrolyte, in order to ensure that the electrolyte contacts the positive electrode active material, the solid electrolyte can also be mixed in the positive electrode material.
[0173] (Shape and structure of all-solid-state batteries)
[0174] Next, examples of arrangement and configuration of components of the all-solid-state battery of the present embodiment will be described.
[0175] The all-solid-state battery composed of the above-mentioned positive electrode, negative electrode and solid electrolyte can be made into various shapes such as coin shape and stacked shape. In the case of any shape, the positive electrode and the negative electrode can be stacked across the solid electrolyte. In addition, the positive electrode collector and the positive terminal leading to the outside and the negative electrode collector and the negative terminal leading to the outside can be connected using a collector lead, and the all-solid-state battery can be made by sealing in a battery case.
[0176] (Characteristics of all-solid-state batteries)
[0177] The all-solid-state battery using the positive electrode active material of this embodiment has a high cycle capacity retention rate (durability), and can be used appropriately when charging and discharging at a high voltage (for example, with a voltage limit of 4.5 V or more based on metal lithium). For example, when the current density is set to 0.2 mA / cm 2 , charged to a cut-off voltage of 4.5 V (vs. Li), and then discharged to a cut-off voltage of 2.5 V (vs. Li) after pausing for 1 hour, the cycle capacity maintenance rate (discharge capacity after 100 cycles / initial discharge capacity (%)) is preferably 75% or more, more preferably 80% or more, and further preferably 90% or more.
[0178] In addition, the all-solid-state battery using the positive electrode active material of this embodiment can exhibit high capacity. For example, the positive electrode active material of this embodiment is used for the positive electrode to form Figure 4 The test cell shown in the figure has a current density of 0.2 mA / cm 2 , charged to a cut-off voltage of 4.5 V (vs. Li), and after pausing for 1 hour, the discharge capacity when discharged to a cut-off voltage of 2.5 V (vs. Li), that is, the initial discharge capacity, is preferably 165 mAh / g or more.
[0179] Example
[0180] Hereinafter, the present invention will be specifically described using Examples and Comparative Examples.
[0181] [Example 1]
[0182] 1. Production of lithium nickel composite oxide
[0183] The lithium nickel composite oxide is produced through the following steps.
[0184] (a) Crystallization process
[0185] 10 L of pure water was added to a reaction tank having an internal volume of 60 L, and the temperature in the tank was maintained at 50° C. with stirring. At this time, the reaction tank was set to a nitrogen atmosphere with an oxygen concentration of 1% by volume or less.
[0186] Appropriate amounts of 25 mass % sodium hydroxide aqueous solution and 25 mass % ammonia water were added to the reaction tank to prepare an initial aqueous solution so that the pH value at a liquid temperature of 25° C. was 12.8 and the ammonia concentration of the solution in the reaction tank was 15 g / L.
[0187] At the same time, nickel sulfate, cobalt sulfate and manganese sulfate were dissolved in pure water so that the mass ratio of nickel, cobalt and manganese was Ni:Co:Mn=0.78:0.11:0.11 to prepare 25 L of a 2.0 mol / L nickel-cobalt-manganese mixed aqueous solution. In addition, 5 L of a 0.37 mol / L aluminum sulfate aqueous solution was prepared.
[0188] To the initial aqueous solution in the reaction tank, 66 mL of a mixed aqueous solution of nickel, cobalt and manganese was added dropwise at 109 mL / min to prepare a reaction aqueous solution. At this time, 25% by mass ammonia water and 25% by mass sodium hydroxide aqueous solution were also added dropwise to the initial aqueous solution at a certain rate, and the pH value of the reaction aqueous solution was controlled to be maintained at 12.8 based on a liquid temperature of 25°C.
[0189] Next, sulfuric acid was added dropwise to the reaction tank to adjust the pH of the reaction aqueous solution to 11.5. This operation is intended to reduce the pH, thereby reducing the rate at which the composite hydroxide of Ni, Co, Mn and Al precipitates from the liquid phase to the solid phase in the subsequent crystallization step (particle growth step), thereby improving the uniformity of the obtained particle size distribution and the sphericity of the particles.
[0190] After controlling the pH, 26.2 L of a mixed aqueous solution of nickel, cobalt and manganese was added to the reaction solution in the reaction tank at 109.2 mL / min, and 5.9 L of an aqueous solution of aluminum sulfate was added at 24.8 mL / min. At this time, 25% by mass ammonia water and 25% by mass sodium hydroxide aqueous solution were also added to the initial aqueous solution at a certain rate, and the pH value of the reaction aqueous solution was maintained at 11.5 based on a liquid temperature of 25° C., and the ammonia concentration was maintained at 15 g / L.
[0191] After all the nickel-cobalt-manganese mixed aqueous solution and aluminum sulfate aqueous solution were dropped, the pH of the reaction aqueous solution in the reaction tank was raised until the pH reached 13.0 based on a liquid temperature of 25° C. This operation is intended to precipitate nickel ions dissolved in the liquid phase by ammine complexation on the hydroxide to obtain the target chemical composition.
[0192] Then, the reaction aqueous solution was subjected to solid-liquid separation using a Buchner funnel, a filter tank and a vacuum pump vacuum filter. Furthermore, the obtained solid phase was dispersed in 20 L of pure water at 40° C. for solid-liquid separation, and this operation was repeated twice to remove water-soluble impurities such as sodium sulfate from the nickel composite hydroxide.
[0193] The cake-like solid phase after solid-liquid separation after washing was dried in a fixed type dryer at 120° C. in an air atmosphere for 24 hours and then passed through a sieve with a mesh size of 100 μm to obtain a powdery nickel composite hydroxide.
[0194] (b) Oxidation roasting process
[0195] The prepared composite hydroxide was calcined at 600° C. for 2 hours in an air atmosphere having an oxygen concentration of 20 vol % using an atmosphere calcining furnace (BM-50100M manufactured by SILICONIT CORPORATION) and then cooled to room temperature to obtain a nickel composite oxide.
[0196] (c) Mixing process
[0197] Lithium hydroxide monohydrate weighed in such a manner that the amount of Li relative to the total amount of Ni, Co, Mn and Al contained in the nickel composite oxide is 103% was added to the nickel composite oxide, and the mixture was mixed using a TURBULA-Shaker mixer (Turbula Shaker Mixer, manufactured by DALTON Co., Ltd., T2F) to obtain a lithium mixture.
[0198] (d) Firing process
[0199] The obtained lithium mixture was calcined at 875° C. for 5 hours in an oxygen-containing atmosphere having an oxygen concentration of 90% by volume or more using an atmosphere calcining furnace (BM-50100M manufactured by SILICONIT CORPORATION), and then cooled to room temperature to obtain lithium nickel composite oxide particles.
[0200] 2. Evaluation of Lithium Nickel Composite Oxide Particles
[0201] The obtained lithium nickel composite oxide was evaluated as follows.
[0202] (a) Composition
[0203] Analysis using an ICP emission spectrometer (725ES, manufactured by VARIAN) confirmed that the amount ratio of Li, Ni, Co, Mn, and Al in the lithium nickel composite oxide was Li:Ni:Co:Mn:Al=1.03:0.750:0.11:0.11:0.03.
[0204] (b) Crystal structure
[0205] The crystal structure of the lithium nickel composite oxide particles was measured using XRD (PROMRD, X'Pert, manufactured by Panalytical Corporation). It was confirmed that the crystal structure was a layered rock salt type crystal structure in which a peak attributed to the R-3m structure was detected in the diffraction pattern.
[0206] In addition, the half-value width of the peak attributed to the (003) plane in the diffraction pattern was measured and the size of the crystallite was calculated using the Scherrer method, and the result was 118 nm.
[0207] (c) Determination of the amount of dissolved lithium ions
[0208] The amount of dissolved lithium ions in the lithium nickel composite oxide was determined by titration. 2.0 g of lithium nickel composite oxide was dispersed in 125 ml of pure water, and 2 mL of 10% barium chloride solution was further added. While stirring, neutralization titration was performed with 1 mol / L hydrochloric acid, and the amount of 1 mol / L hydrochloric acid required until the inflection point near pH 4 of the obtained titration curve was converted into the amount of Li derived from dissolved lithium ions. As a result, the amount of dissolved lithium ions in the lithium nickel composite oxide was 0.17 wt%.
[0209] (d) Specific surface area
[0210] The BET specific surface area of the lithium nickel composite oxide was measured using a fully automatic BET specific surface area measuring device (Macsorb, manufactured by Mountech Co., Ltd.) and was confirmed to be 0.56 m 2 / g.
[0211] (e) Particle size distribution
[0212] The particle size distribution of the lithium nickel composite oxide was measured using a laser diffraction scattering particle size distribution measuring device (Microtrac HRA, manufactured by Nikkiso Co., Ltd.). The results showed that the volume-based average particle size D50 was 4.9 μm, and the average particle size D10, D90, and M V Calculated deviation index ((D90-D10) / M V ) is 0.43.
[0213] 3. Coating of lithium nickel composite oxide
[0214] The obtained lithium nickel composite oxide was subjected to the following coating step.
[0215] In a solution prepared by adding 30 ml of isopropyl alcohol (IPA) and 1.8 g of tetrabutoxytitanium (Ti-BuOH) and stirring, a solution prepared by adding 20 ml of IPA and 0.9 g of acetylacetone was added dropwise at 60°C while heating and stirring. This is to avoid adding high concentrations of acetylacetone directly to the Ti solution. Then, a solution prepared by adding 0.54 g of pure water to 10 ml of IPA was added to the cooled solution. Finally, 65 ml of IPA was added to the obtained solution to adjust the coating solution.
[0216] Using the coating solution, 500 g of the lithium nickel composite oxide was coated using a roll flow coating device (MP-01, POWREX).
[0217] Using a flow rate of 0.3m / s heated to 120°C 3 500 g of lithium nickel composite oxide was flowed in the chamber by air at a flow rate of / h, and the coating liquid was sprayed on the lithium nickel composite oxide at a flow rate of 1.7 ml / min.
[0218] After the coating liquid was completely sprayed, the lithium nickel composite oxide was recovered from the chamber and heat treated at 400° C. for 5 hours under oxygen flow using an atmosphere sintering furnace (BM-50100M manufactured by SILICONIT Co., Ltd.). Then, it was cooled to room temperature to obtain lithium nickel composite oxide particles (positive electrode active material) having a coating layer (containing Li and Ti).
[0219] 4. Evaluation of Lithium Nickel Composite Oxide Particles Having a Coating Layer
[0220] (a) Composition
[0221] Analysis using an ICP emission spectrometer (Varian, 725ES) confirmed that the coated lithium nickel composite oxide contained 0.88 wt% Ti and the amount of Ti per unit area of the base material was 370 μmol / m 2 .
[0222] (b) Thickness of coating layer
[0223] The coated lithium nickel composite oxide sliced with CRYO ION SLICER (JEOL, IB-09060CIS) was observed using TEM (JEOL, JEM-ARM200F), and it was confirmed that the thickness of the coating layer was 11 nm.
[0224] 5. Fabrication of all-solid-state secondary batteries
[0225] In the capacity evaluation of the obtained positive electrode active material, the Figure 4 A battery with the structure shown (hereinafter referred to as a "test battery").
[0226] (Constitution of the test battery)
[0227] like Figure 4 As shown, the test battery SBA includes a case having a negative electrode can NC and a positive electrode can PC, and a powder compact unit C accommodated in the case.
[0228] The shell has a negative electrode tank NC which is hollow and opened at one end, and a positive electrode tank PC which is arranged at the opening of the negative electrode tank NC. In addition, a space for accommodating a powder compact unit C is formed between the positive electrode tank PC and the negative electrode tank NC. The positive electrode tank PC is fixed to the negative electrode tank NC, for example, by a butterfly screw SW. In addition, the negative electrode tank NC has a negative electrode terminal, and the positive electrode tank PC has a positive electrode terminal. In addition, the shell has an insulating sleeve ISV. The insulating sleeve ISV is used to fix the negative electrode tank NC and the positive electrode tank PC in a manner that a non-contact state is maintained.
[0229] A pressure screw PSW is provided at one closed end of the negative electrode tank NC. After the positive electrode tank PC is fixed to the negative electrode tank NC, the pressure screw PSW is tightened toward the storage space of the powder compact unit C, thereby maintaining the powder compact unit C in a pressurized state through the hemispherical gasket W. In addition, a screw-in plug P is provided at one end of the negative electrode tank NC where the pressure screw PSW is provided. An O-ring OL is provided between the negative electrode tank NC and the positive electrode tank PC, and between the negative electrode tank NC and the plug P, and the gap between the negative electrode tank NC and the positive electrode tank PC is sealed to maintain the airtightness in the housing.
[0230] The compressed powder unit C is a granular material in which the positive electrode layer PL, the solid electrolyte layer SEL and the negative electrode layer NL are stacked in sequence. The positive electrode layer PL contacts the inner surface of the positive electrode can PC through the lower current collector LCC. The negative electrode layer NL contacts the inner surface of the negative electrode can NC through the upper current collector UCC, the hemispherical gasket W and the pressure screw PSW. The lower current collector LCC, the compressed powder unit C and the upper current collector UCC are protected by the sleeve SV to prevent the positive electrode layer PL and the negative electrode layer NL from electrical contact.
[0231] (Production of Evaluation Batteries)
[0232] The test battery SBA was produced as follows.
[0233] First, 80 mg of the synthesized solid electrolyte was pressurized at 25 MPa using a pelletizer to obtain Solid electrolyte pellets. Next, 70 mg of the positive electrode active material and 30 mg of the solid electrolyte are mixed in a mortar. 15 mg of the solid electrolyte pellets and the mixture of the positive electrode active material + solid electrolyte are placed in a pellet former and pressurized at 360 MPa to form a positive electrode layer on the solid electrolyte pellets. From bottom to top, the lower current collector LCC, the pellets arranged with the positive electrode layer PL facing downward, the indium (In) foil (negative electrode layer NL), and the upper current collector UCC are stacked in sequence and pressurized at 9 kN to form an electrode (compressed powder unit C). The electrode (compressed powder unit C) is sealed in a shell and the pressure screw is tightened with a torque of 6 to 7 N·m. The test battery SBA is manufactured in a glove box with an Ar atmosphere where the dew point is controlled to -80°C.
[0234] 6. Evaluation of all-solid-state secondary batteries
[0235] The charge and discharge capacity indicating the performance of the produced test battery was evaluated as follows.
[0236] (a) Initial discharge capacity
[0237] The initial discharge capacity was evaluated as follows: a test battery with an indium foil as the negative electrode was prepared and left to stand for about 24 hours. After the open circuit voltage (OCV) stabilized, the current density to the positive electrode was set to 0.2 mA / cm 2 The battery was charged to a cut-off voltage of 4.5 V (vs. Li), and after a 1-hour pause, it was discharged to a cut-off voltage of 2.5 V (vs. Li), and the discharge capacity (initial discharge capacity) at this time was measured for evaluation. The measurement result was 168 mAh / g.
[0238] (b) Cycle capacity maintenance rate
[0239] The current density to the positive electrode was set to 0.2 mA / cm 2 , charged to a cut-off voltage of 4.5 V (vs. Li), discharged to a cut-off voltage of 2.5 V (vs. Li), repeated 100 cycles, and the ratio of the capacity after 100 cycles to the initial discharge capacity was evaluated as the capacity retention rate.
[0240] [Example 2]
[0241] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the Li / M ratio in the lithium nickel composite oxide synthesis step of Example 1 was 1.05.
[0242] [Example 3]
[0243] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al in the lithium nickel composite oxide synthesis step of Example 1 was 0.75:0.05:0.17:0.03.
[0244] [Example 4]
[0245] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al in the lithium nickel composite oxide synthesis step of Example 1 was 0.65:0.16:0.16:0.03.
[0246] [Example 5]
[0247] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al in the lithium nickel composite oxide synthesis step of Example 1 was 0.65:0.08:0.24:0.03.
[0248] [Example 6]
[0249] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al in the lithium nickel composite oxide synthesis step of Example 1 was 0.55:0.21:0.21:0.03.
[0250] [Example 7]
[0251] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the ratio of Ni:Co:Mn:Al in the lithium nickel composite oxide synthesis step of Example 1 was 0.55:0.10:0.32:0.03.
[0252] [Comparative Example 1]
[0253] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the Li / M ratio in the lithium nickel composite oxide synthesis step of Example 1 was 1.08.
[0254] [Comparative Example 2]
[0255] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the average particle size D50 in the lithium nickel composite oxide synthesis step of Example 1 was 11.3 μm.
[0256] [Comparative Example 3]
[0257] The coated lithium nickel composite oxide was synthesized under the same conditions as in Example 1 except that the coating of the lithium nickel composite oxide particles in Example 1 was not performed.
[0258] [Table 1]
[0259]
[0260] [Evaluation results]
[0261] The positive electrode active material of the embodiment has a high initial charge capacity, and the cycle capacity maintenance rate of the all-solid-state battery is significantly improved compared with the positive electrode active material of Comparative Example 1 (Li site occupancy greater than 98.5%). In particular, in Examples 5 and 7 where the Li site occupancy is low, the cycle capacity maintenance rate is significantly improved.
[0262] On the other hand, in the case of the positive electrode active material of Comparative Example 2 having a large average particle diameter D50 (11.3 μm), the cycle capacity retention rate was low.
[0263] In addition, in the case of the positive electrode active material of Comparative Example 3 manufactured under the same conditions as Example 1, except for not having a coating layer, the cycle capacity retention rate of the all-solid-state battery is very low. This is considered to be because there is no coating layer on the surface of the lithium nickel composite oxide particles, so the interface resistance between the positive electrode active material and the solid electrolyte increases.
[0264] According to the present invention, it is possible to provide a positive electrode active material that can be suitably used in a positive electrode of an all-solid-state lithium ion secondary battery that requires a high battery capacity, and a method for producing the same.
[0265] It should be noted that the technical scope of the present invention is not limited to the methods described in the above-mentioned embodiments, etc. One or more of the elements described in the above-mentioned embodiments, etc. are sometimes omitted. In addition, the elements described in the above-mentioned embodiments, etc. can be appropriately combined. And, as long as the law permits, the disclosures of Japanese Patent Application Nos. 2022-157076 and 2022-084101, which are Japanese patent applications, and all the documents cited in the above-mentioned embodiments, etc. are cited as part of the description herein.
[0266] Description of Reference Numerals
[0267] 1: Lithium nickel composite oxide particles,
[0268] 2: coating layer,
[0269] 10: positive electrode active material,
[0270] SBA: test battery,
[0271] PC: positive electrode tank,
[0272] NC: Negative tank,
[0273] ISV: Insulation Sleeve,
[0274] C: Powder pressing unit,
[0275] PL: positive electrode layer,
[0276] NL: negative electrode layer,
[0277] SEL: solid electrolyte layer,
[0278] LCC: Lower Current Collector,
[0279] UCC: Upper Current Collector,
[0280] P: plug,
[0281] PSW: Pressure Screw,
[0282] W: hemispherical gasket,
[0283] OL: O-ring,
[0284] SV: Sleeve,
[0285] SW: screw,
[0286] N: Nut.
Claims
1. A positive electrode active material for all-solid-state lithium-ion secondary batteries, which has particles of a lithium nickel composite oxide and a coating layer covering the surface of the particles, The lithium nickel composite oxide particles have a crystal structure belonging to the space group R-3m, and contain at least Li, Ni, Mn and element M, wherein the mass ratio of the elements is represented by Li:Ni:Mn:M=a:(1-xy):x:y, wherein: 0.95 ≤ a ≤ 1.10, 0 < x ≤ 0.5, 0 < y ≤ 0.5, 0 < x + y ≤ 0.7, and the element M is at least one selected from the group consisting of Co, Al, Zr, Si, Zn, Nb, and Ti, The Li site occupancy rate is 92% or more and 98.5% or less, In the cumulative volume distribution curve of the particle size distribution, the particle diameter D50 corresponding to a cumulative volume rate of 50% is 8 μm or less, The crystallite diameter calculated by the Scherrer method from the diffraction peak attributed to the (003) plane measured by XRD is 70 nm or more and 140 nm or less, The amount of eluted lithium ions determined by neutralization titration is 0.05 mass% or more and 0.50 mass% or less relative to the total amount of the particles of the lithium nickel composite oxide, The coating layer is a composite oxide containing Li and at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W.
2. The positive electrode active material for an all-solid-state lithium-ion secondary battery according to claim 1, wherein The lithium nickel composite oxide particles include secondary particles formed by agglomeration of a plurality of primary particles, have a porous structure having a plurality of voids in the secondary particles where the primary particles do not exist, and have a specific surface area of 0.3 m2 as measured by a nitrogen adsorption BET method. 2 / g or more and 2.0m 2 / g or less.
3. The positive electrode active material for an all-solid-state lithium-ion secondary battery according to claim 1 or 2, wherein The average thickness of the coating layer is 1 nm or more and 15 nm or less.
4. A method for manufacturing a positive electrode active material for all-solid-state lithium-ion secondary batteries according to claim 1 or 2, which comprises: A mixing step of mixing a nickel composite compound and a lithium compound to obtain a mixture; A firing step of firing the mixture to obtain the particles of the lithium nickel composite oxide; and A coating step of causing a coating liquid containing at least one element selected from the group consisting of Al, Si, Ti, V, Ga, Ge, Zr, Nb, Mo, Ta, and W to adhere to the surface of the particles of the lithium nickel composite oxide to form the coating layer.
5. The method for producing a positive electrode active material for an all-solid-state lithium-ion secondary battery according to claim 4, wherein: The nickel composite compound contains a nickel composite oxide, The method for manufacturing a positive electrode active material for all-solid-state lithium-ion secondary batteries comprises an oxidation roasting step of subjecting a nickel composite hydroxide adjusted by a crystallization reaction to oxidation roasting to obtain the nickel composite oxide.
6. The method for producing a positive electrode active material for an all-solid-state lithium-ion secondary battery according to claim 4, wherein: After the coating step, there is a heat treatment step of heat-treating the particles of the lithium nickel composite oxide having the coating layer formed on the surface at 300°C or higher.
Citation Information
Patent Citations
Material for positive electrode active material
JP2010170715A
Nickel-cobalt-manganese complex hydroxide particle and method of producing the same, positive electrode active material for nonaqueous electrolyte secondary battery and method of producing the same, and nonaqueous electrolyte secondary battery
JP2011116580A
Sulfide solid electrolyte
JP2014056661A
Ultraviolet ray irradiation apparatus
JP2022084101A
Management system, server, access management device and working robot
JP2022157076A